2021
DOI: 10.1038/s41419-021-03709-5
|View full text |Cite
|
Sign up to set email alerts
|

Permissive effect of GSK3β on profibrogenic plasticity of renal tubular cells in progressive chronic kidney disease

Abstract: Renal tubular epithelial cells (TECs) play a key role in renal fibrogenesis. After persistent injuries that are beyond self-healing capacity, TECs will dedifferentiate, undergo growth arrest, convert to profibrogenic phenotypes, and resort to maladaptive plasticity that ultimately results in renal fibrosis. Evidence suggests that glycogen synthase kinase (GSK) 3β is centrally implicated in kidney injury. However, its role in renal fibrogenesis is obscure. Analysis of publicly available kidney transcriptome dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Whether this pathway also regulates EphB2 in the kidney during injury is not investigated yet. Interestingly, GSK-3β has been recently implicated in the pathogenesis of kidney injury [ 35 ]. On the other hand, it is likely that up-regulation/activation of EphB2 upon kidney injury may aggravate kidney cell injury, death, and EMT and thereby causing renal fibrosis via multiple pathways, including potentiation of NF-κB-mediated inflammation response, activation of TGFβ1/Smad3-mediated EMT and other pathways, as indicated by the NanoString gene expression and verified by the signaling assessment in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this pathway also regulates EphB2 in the kidney during injury is not investigated yet. Interestingly, GSK-3β has been recently implicated in the pathogenesis of kidney injury [ 35 ]. On the other hand, it is likely that up-regulation/activation of EphB2 upon kidney injury may aggravate kidney cell injury, death, and EMT and thereby causing renal fibrosis via multiple pathways, including potentiation of NF-κB-mediated inflammation response, activation of TGFβ1/Smad3-mediated EMT and other pathways, as indicated by the NanoString gene expression and verified by the signaling assessment in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…19,21,47,48 However, this article will focus on a very popular kidney disease animal model, the folic acid (FA)-induced rodent model involving the use of both mouse and rat. [49][50][51][52][53] A comparison of the FA model with other chemically induced kidney injury animal models is given in Table 1.…”
mentioning
confidence: 99%
“…Glycogen synthase kinase 3β (GSK‐3β) is a serine/threonine‐protein kinase that functions as an integration point for multiple cellular pathways including PTEN/PI3K/AKT signaling, which are involved in glycogen biosynthesis, inflammation, mitochondrial dysfunction, and apoptosis (Beurel et al, 2015; Doble & Woodgett, 2003). Recent studies have shown that GSK‐3β plays an important role in the development of renal fibrosis (B. Chen et al, 2021; Lu et al, 2019). As PTEN regulates GSK‐3β activities via PI3K, it will be interesting to examine if PTEN/GSK‐3β signaling pathway is involved in AngII‐induced renal inflammation and fibrosis in the future study.…”
Section: Discussionmentioning
confidence: 99%